Relationships between residents attitude, local authority governance and solid waste collection at Jigawa State, Nigeria - Aminu, Mansur (2023)
The relationships between residents’ attitude, local authority governance and solid waste collection in Jigawa State are related to the wider issue of the failure of governance. Deficiencies in the delivery of solid waste collection services in the region are often symbolic of its form of governance. Poor governance has hampered the solid waste management sector for many years (Ezeah and Roberts 2014). Effective provision of solid waste collection services in an indicator of good urban governance (Nzeadibe and Anyadike 2012), which is far from reality in Jigawa state. In order to achieve viable solid waste management, good governance plays a critical role (Onibokun 1999). Solid waste collection become a major issue of concern for most cities of Jigawa State. Efficient delivery of solid waste collection services remains a distant hope, mainly because local authorities could not provide the services. That is why the community needs to manage their waste, the region has 27 Local Authority areas each with no defined solid waste collection services except one in Dutse (Capital). This study's objective is to evaluate the relationships between residents’ attitudes, Local authority governance and solid waste collection in Jigawa state, Nigeria. The quantitative technique was used in data collection; convenient sampling was used to select the respondents from Nine (9) non-service areas selected from three senatorial districts. Multi-stage sampling technique was used to administer the questionnaire to the respondents.The data was analysed using descriptive statistics with frequency and percentage. A Pearson correlation was used to determine the relationships between variables. The outcome of the study revealed that the fundamental problem that emerged was that solid waste was not governed in an integrated manner, and Local authorities failed to meet the growing demand for service delivery. The study concludes that poor governance has encumbered the waste management sector and therefore, fundamental changes are essential if a viable solid waste management system is to be established.